The chemical, phase composition and optical properties of ZnxCd₁-xS films obtained by close spaced vacuum sublimation - Yeromenko, Yu.; Opanasyuk, A.; Voznyi, A.; Shpetnyi, I.; Gnatenko, Yu.; Grebinaha, V. (Functional Materials, 2019)
The optical properties, chemical and phase composition of ZnxCd₁-xS films obtained by close-spaced vacuum sublimation (CSS) were studied using X-ray diffraction, energy dispersive X-ray analysis and optical spectroscopy methods. The solid solution films were deposited at the substrate and evaporator temperatures of Ts = 573 K and Te = 1273 K, respectively. ZnS and CdS powders were mixed with different weight ratios (x = 0; 0.2; 0.4; 0.6; 0.8; 1.0) for further deposition of ZnxCd₁-xS films. It was found that the optical properties (band gap, transmission and absorption coefficients) of ZnxCd₁-xS films depends on the chemical composition and can be controlled by the weight percentages of the initial powders. It was found that the actual zinc concentrations in the films is higher than expected and the film thickness reduces with increasing of x. This results demonstrate that ZnxCd₁-xS solid solutions films obtained by CSS have improved optical parameters, high crystal quality and good stoichiometry.